2019
DOI: 10.3892/ol.2019.10151
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy‑guided long intestinal tube placement for the treatment of malignant bowel obstruction

Abstract: The aim of the present study was to investigate the safety and efficacy of long intestinal tube placement under fluoroscopic guidance for the treatment of malignant bowel obstruction (MBO). The cases of 74 patients with MBO who underwent long intestinal tube placement under fluoroscopic guidance during the period between June 2015 and October 2017 were reviewed. The clinical characteristics were retrospectively analysed with respect to efficacy, safety and outcome. Long intestinal tube placement was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Drainage decompression is more common in the single application of nasoileus catheter or transanal ileus catheter, especially for the relief of abdominal distension and abdominal pain and other related clinical symptoms. Lai et al reported that fluoroscopy-guided placement of long intestinal canal in the treatment of severe malignant intestinal obstruction, and the symptom relief rate of abdominal pain and vomiting are very high, and the incidence of serious complications is very low (18); however, it is difficult to achieve rapid improvement of symptoms for complex malignant intestinal obstruction through a separate drainage approach.…”
Section: Discussionmentioning
confidence: 99%
“…Drainage decompression is more common in the single application of nasoileus catheter or transanal ileus catheter, especially for the relief of abdominal distension and abdominal pain and other related clinical symptoms. Lai et al reported that fluoroscopy-guided placement of long intestinal canal in the treatment of severe malignant intestinal obstruction, and the symptom relief rate of abdominal pain and vomiting are very high, and the incidence of serious complications is very low (18); however, it is difficult to achieve rapid improvement of symptoms for complex malignant intestinal obstruction through a separate drainage approach.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, we inserted the nasointestinal tube with continuous negative pressure suction, without placement of a mental stent, which also achieved a satisfactory outcome. Zhang et al [ 27 ] analyzed 74 patients with malignant bowel obstruction treated with the fluoroscopy-guided long intestinal tube placement and showed that the symptoms of 58 patients improved significantly. At 1-mo follow-up, the symptoms of obstruction did not deteriorate.…”
Section: Discussionmentioning
confidence: 99%
“…Long intestinal tube (LIT) decompression is a useful treatment for patients with bowel obstruction, achieved by draining the intestinal contents [1,2]. While gastrointestinal bleeding, perforation, laryngeal injury, and aspiration pneumonia are well-known complications of LIT insertion, submucosal tunnel formation is a very rare complication [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%